Literature and Society in the Fourth Century AD : Performing Paideia, Constructing the Present, Presenting the Self - Hoof, Lieve van (Mnemosyne, Supplements Ser, 2014)
Contents -- Abbreviations -- Notes on the Contributors -- 1 The Social Role and Place of Literature in the Fourth Century AD -- 2 Literary History: A Fourth-Century Roman Invention? -- 3 Militia philosophorum: Le rôle des lettrés dans l'entourage des empereurs romains du IVe siècle -- 4 Gregory's Governors: Paideia and Patronage in Cappadocia -- 5 Lobbying through Literature: Libanius, For the Teachers (Oration 31) -- 6 Texts, Teachers and Pupils in the Writings of Gregory of Nyssa -- 7 Unreliable Witness: Failings of the Narrative in Ammianus Marcellinus -- 8 A Living Relic for the Vicar of Rome: Strategies of Visualization in a Civil Case -- 9 A Hero in our Midst: Stilicho as a Literary Construct in the Poetry of Claudian -- 10 The Apostles as Instruments of Social Engagement: The Poetical Representation of the Apostles as a Means of Influencing Society -- 11 A War of Words: Sermons and Social Status in Constantinople under the Theodosian Dynasty -- Bibliography -- Index.